To multiply the polynomials \( (2r - 5)(r + 4) \), we can use the distributive property (also known as the FOIL method for binomials).
-
First: Multiply the first terms: \[ 2r \cdot r = 2r^2 \]
-
Outer: Multiply the outer terms: \[ 2r \cdot 4 = 8r \]
-
Inner: Multiply the inner terms: \[ -5 \cdot r = -5r \]
-
Last: Multiply the last terms: \[ -5 \cdot 4 = -20 \]
Now, combine all these results: \[ 2r^2 + 8r - 5r - 20 \]
Combine the like terms \( 8r \) and \( -5r \): \[ 2r^2 + (8r - 5r) - 20 = 2r^2 + 3r - 20 \]
So, the final result of multiplying the polynomials is: \[ \boxed{2r^2 + 3r - 20} \]